Sex and Eroticism in Mesopotamian Literature - Leick, Dr Gwendolyn, author.
1 online resource (336 pages)
Keywords: Sex and Eroticism in Mesopotamian Literature is a new contribution to current debates about sex and eroticism. It gives an insight into Mesopotamian attitudes to sexuality by examining the oldest preserved written evidence on the subject - the Sumero-Akkadian cuneiform sources - which were written between the 21st and the 5th centuries B.C. Using these long-neglected and often astonishing data, Gwendolyn Leick is able to anlayse Mesopotamian views of prostitution, love magic and deviant sexual behaviour as well as more general issues of sexuality and gender. This fascinating book sheds light on the sexual culture of one of the earliest literate civilisations.